2010
DOI: 10.1051/0004-6361/201014865
|View full text |Cite
|
Sign up to set email alerts
|

On the suspected timing error in Wilkinson microwave anisotropy probe map-making

Abstract: Context. It has recently been suggested that the compilation of the calibrated time-ordered-data (TOD) of the Wilkinson Microwave Anisotropy Probe (WMAP) observations of the cosmic microwave background (CMB) into full-year or multi-year maps may have been carried out with a small timing interpolation error. A large fraction of the previously estimated WMAP CMB quadrupole signal would be an artefact of incorrect Doppler dipole subtraction if this hypothesis were correct. Aims. Since observations of bright foreg… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
16
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 36 publications
4
16
0
Order By: Relevance
“…In previous works (Liu et al 2010; Moss et al 2011; Roukema 2010a), it has been discovered and confirmed that, given Δ t ∼−25.6 ms and without using any CMB data, an artificial quadrupole component that is very similar to the released WMAP CMB quadrupole can be produced (Fig. 2).…”
Section: Consequence Of the Timing Offsetsupporting
confidence: 63%
See 1 more Smart Citation
“…In previous works (Liu et al 2010; Moss et al 2011; Roukema 2010a), it has been discovered and confirmed that, given Δ t ∼−25.6 ms and without using any CMB data, an artificial quadrupole component that is very similar to the released WMAP CMB quadrupole can be produced (Fig. 2).…”
Section: Consequence Of the Timing Offsetsupporting
confidence: 63%
“…In the WMAP TOD archive, each science frame contains 15–30 observations, and each observation last for a duration τ of 102.4, 76.8 and 51.2 ms for Q ‐, V ‐ and W ‐band, respectively. Following the convention used in previous works (Liu et al 2010; Roukema 2010a,b), the timing offset used in this work is a relative one, given in percentage of the duration τ of each observation where t D is the time for the instantaneous Doppler dipole signal D (w) and t 0 is the starting time of each observation. If the time used for the science data and spacecraft attitude data are synchronous, then the time for the instantaneous Doppler dipole signal D (w) should be at the centre of each observation and Δ t r = 0.5 (same for all bands, neglecting the τ difference, which is why the relative time Δ t r is preferred).…”
Section: Checking the Timing Offsetmentioning
confidence: 99%
“…There are still some authors who doubt this fact, pointing out that there are spurious temperature anisotropies that are comparable with the entire signal [195,196,197], or testing the null hypothesis that the Time-Ordered-Data (TOD) were consistent with no anisotropies when hourly calibration parameters were allowed to vary, i.e. that sky maps with no anisotropies outside the galactic band other than the dipole were a better fit to the uncalibrated TOD than those from the official analysis [198].…”
Section: Microwave Background Radiation Anisotropiesmentioning
confidence: 99%
“…Recently, Roukema [3,14] have pointed out that a small timing error during calibration of the raw TOD could correspond to the addition of a pseudo-dipole difference signal with no effect on positional data.…”
Section: Discussionmentioning
confidence: 99%